Determinan Ekspor RPO Indonesia di Pasar Organisasi Kerjasama Islam - Yarasevika, Samara; Suharno, Suharno; Nurmalina, Rita (Jurnal Agribisnis Indonesia, 2022)
Indonesia has been the largest exporter of Refined Palm Oil (RPO) in the world which OIC countries being main export destination markets. However, most of Indonesian RPO exports to the OIC countries are still concentrated in four countries, namely Pakistan, Malaysia, Bangladesh, and Egypt. The distribution of Indonesian RPO exports to the OIC countries is still in small number due to the high tariff applied by several OIC countries. This research aims to analyze the factors that influence Indonesian palm oil trade in 20 OIC countries. The analysis methods used Gravity Model and Trade Potential Analysis. The result using gravity model showed that the real GDP per capita of destination countries, the real GDP per capita of Indonesia, exchange rate, price, tariff, and the RCA index of Indonesian RPO in destination countries are significantly influence its volume exports. On the other hand, economic distance and population of destination countries do not have a significant effect on the RPO export volume.